KINETIKA REAKSI HIDROLISA LMWCS (LOW MOLECULAR WEIGHT CHITOSAN) MENGGUNAKAN ASAM KLORIDA - Indrawati Dwi Paramita; Ressa Puspita Dewi; Aji Prasetyaningrum (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Chitosan is a natural carbohydrate biopolymer derived from crustacea exoskeleton animals which have important benefits in the health field. Quality and utilization of chitosan depends on the molecular weight and degree of deacetilation. The purpose of this research was to determine the effect of temperature and time on the rate of depolymerization of chitosan from high to low molecular weight, as well as experimental data applied to the modeling of reaction kinetics of hydrolysis of variation LMWCs (Low Molecular Weight Chitosan) desired (+20 kDa). Chitosan hydrolysis process carried out with distilled water to be included in the reactor equipped with stirrer, then heated until it reaches a certain temperature. Once the desired temperature is reached, the chitosan powder introduced into the reactor and followed by the introduction of the catalyst. Hydrolysis process carried out during a certain time (corresponding variable) with stirring and the temperature is kept constant (as variables). After the hydrolysis process is over, done by adding a solution of NaOH neutralization. The solid obtained was then filtered, washed with water and dried. The higher the temperature of hydrolysis, the hydrolysis will take place more rapidly with stirring and the use of a strong acid with a high concentration. The longer of the hydrolysis time (15-120 min) led to a decline in the value of molecular weight (MW) are obtained. Iteration of the experimental data, obtained the value of k1 = 3.145x10-6 and k2 =1.84x10-6.The value of k1 and k2 are used to make the modeling of the kinetics of the hydrolysis reaction LMWCs desired variation, so it can be determined the estimated time required to process the hydrolysis of chitosan.